2020
DOI: 10.21203/rs.3.rs-91068/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of EZH2 prevents acute respiratory distress syndrome (ARDS)-associated pulmonary fibrosis by regulating the macrophage polarization phenotype

Abstract: Background: We recently reported histone methyltransferase enhancer of zeste homolog 2 (EZH2) as a key epigenetic regulator that contributes to the dysfunction of innate immune responses to sepsis and subsequent lung injury by mediating the imbalance of macrophage polarization. However, the role of EZH2 in acute respiratory distress syndrome (ARDS)-associated fibrosis remains poorly understood. Methods: In this study, we investigated the role and mechanisms of EZH2 in pulmonary fibrosis in a murine model of LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Analysis of BALF was conducted and wet/ dry weight ratio was calculated as we previously described [13]. Macrophages were isolated from BALF and lung tissue homogenates according to our previously reported methods [13,16]. All samples and isolated cells are stored at −20 °C for determinations.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of BALF was conducted and wet/ dry weight ratio was calculated as we previously described [13]. Macrophages were isolated from BALF and lung tissue homogenates according to our previously reported methods [13,16]. All samples and isolated cells are stored at −20 °C for determinations.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, EZH2 might be the targeted gene of miR-138-5p. As we had reported that EZH2 was involved in the activation of M1 macrophage and inhibition of M2 differentiation [16], we hypothesized that circN4bp1 regulates macrophage differentiation through preventing EZH2 downregulation by miR-138-5p. To test this hypothesis, we overexpressed miR-138-5p mimics in the aforementioned two macrophage cell lines and found that the expression level of EZH2 was increased in the presence of the circN4bp1 overexpression (Figure 6(c)), whereas miR-138-5pmimics significantly inhibited the upregulation of EZH2 after the circN4bp1 overexpression (Figures 6(d) and 6(e)).…”
Section: Circn4bp1-mir-138-5p Cerna Modulates Macrophagementioning
confidence: 98%
See 3 more Smart Citations